Plasma immersion ion charge state and mass spectrometer; Review of Scientific Instruments; Vol. 85, iss. 2 - Stepanov I. B. Igor Borisovich; Ryabchikov A. I. Aleksandr Ilyich; Ananin P. S. Petr Semenovich; Dektyarev S. V. Sergey Valentinovich; Sivin D. O. Denis Olegovich; Verigin D. A. Dan Aleksandrovich (2014, 2014)
Title screen